Analisis Kelayakan Investasi dan Strategi Pembiayaan Pusat Perawatan Postpartum (Studi Kasus: PT Nuno Care) - Nurul Hakiki; Dimas Angga Negoro; Unggul Kustiawan; Mohamad Reza Hilmy (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Indonesia is one of the ASEAN countries with a high maternal mortality rate, partly due to postpartum depression. Postpartum depression has a more severe impact than baby blues, with a recovery period of up to six months. During the postpartum period, women often experience fatigue, fluctuations in appetite, mood swings, sleep disturbances, and physical discomfort due to cesarean section or normal delivery. Support such as adequate rest, healthy nutrition, and attention from partners and the environment are essential. Not only mothers, fathers also have the potential to experience postpartum depression. Risk factors include bipolar disorder, family history of depression, drug abuse, difficulty breastfeeding, and young pregnancy. Therefore, two out of a thousand mothers giving birth are at risk of experiencing mental disorders. Peer support and counseling by professional health practitioners are the main interventions in postpartum depression care. This study aims to assess the feasibility of PT Nuno Care's business in terms of investment and revenue projections, identify optimal funding sources for service development, determine short-term and long-term financial strategies for business sustainability and design a financial model that includes operational costs, service rates, and profitability strategies.